Reliability of estimating active drag using the assisted towing method (atm) with fluctuating velocity - Hazrati, P.; Mason, B.; Sinclair, P. J. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The aim of this study was to examine the reliability of active drag values obtained using a method that compared free swim velocity with measurements taken by towing swimmers slightly faster than their maximum swim speed, while allowing for intra stroke velocity fluctuations. Using nine national level swimmers on two alternate days, reliability was determined using within-subject intra-class correlation coefficients (ICC) within each day and between the days. The ICCs for days one and two were 0.80 and 0.84 respectively, while the comparison of mean active drag values between days was 0.92. Results found that the ATM method with fluctuating velocity to be only moderately reliable within a single test. Taking average values improved this reliability, even when measured over different days. Further investigation is suggested to improve the current method.